Pengembangan Media Kontekstual Biopori pada Topik Penyelamat Bumi dalam Mata Pelajaran Ipas untuk Siswa Kelas VI Sekolah Dasar - Wulandari, Devi Diah; Astutik, Leny Suryaning (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Science learning on the topic of Earth Savior is still dominated by theoretical delivery of material so that students have difficulty linking the concept of environmental conservation with problems they encounter in everyday life. This condition indicates the need for contextual learning media that can provide a more meaningful learning experience. This study aims to develop contextual learning media based on biopores and test its level of validity and practicality as a science learning medium for sixth grade students of SD Negeri 1 Rejoagung, Tulungagung Regency. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of material experts, media experts, and 11 sixth grade students. Data were collected through expert validation sheets and student response questionnaires, then analyzed descriptively quantitatively and qualitatively. The results showed that the media obtained a validity level of 92.5% from material experts and 80% from media experts with a valid category, while the practicality test obtained a percentage of 95.91% with a very practical category. Thus, the biopore-based contextual learning media is declared valid and practical for use in science and science learning. This research was limited to testing validity and practicality, so testing the media's effectiveness on learning outcomes has not been conducted, creating an opportunity for further research.